PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS II-A PADA MATERI KATA TANYA DI SDIT AL-FATHIMIYYAH SURABAYA - Mohammad Qomaruddin; Yuni Gayatri; Ni Luh Putu Sari Murthi (Universitas Muhammadiyah Surabaya, 2024)
This research aims to improve the learning outcomes of class II-A students at SDIT Al-Fathimiyyah through the application of the Problem Based Learning model to question word material. The type of research used is quasi-experimental research. The research design is a post-test only control group design. The research subjects were 29 class II-A students at SDIT Al-Fathimiyyah in the 2023-2024 school year. Data collection techniques are by means of observation and tests. The research instruments used learning implementation observation sheets, cognitive test sheets, and attitude and skills observation sheets. Data analysis was carried out using descriptive and qualitative statistics. The results of this research show that all stages of Problem Based Learning were carried out well, the results of observations of students' attitudes showed that 90% met classical completeness, student learning results showed that 90% met the KKTP, the results of students' skills in presentations showed that 93% met classical completeness. The results of the reflection showed that all students felt happy and could understand the material being taught. The conclusion of this research is that the application of the Problem Based Learning model is effective in improving student learning outcomes.